Green phenolic resins from oil palm Empty Fruit Bunch (EFB) phenolated lignin and bio-oil as phenol substitutes for bonding plywood - Kah, Yen Lim; Tengku Yasim-Anuar, Tengku Arisyah; Sharip, Nur Sharmila; Aziz Ujang, Farhana; Husin, Hazwani; Ariffin, Hidayah; Md Tahir, Paridah; Xinping, Li; Seng, Hua Lee; Yusof, Mohd Termizi (Multidisciplinary Digital Publishing Institute, 2023)
Lignin is a natural biopolymer with a complex three-dimensional network and it is rich in phenol, making it a good candidate for the production of bio-based polyphenol material. This study attempts to characterize the properties of green phenol-formaldehyde (PF) resins produced through phenol substitution by the phenolated lignin (PL) and bio-oil (BO), extracted from oil palm empty fruit bunch black liquor. Mixtures of PF with varied substitution rates of PL and BO were prepared by heating a mixture of phenol–phenol substitute with 30 wt.% NaOH and 80% formaldehyde solution at 94 °C for 15 min. After that, the temperature was reduced to 80 °C before the remaining 20% formaldehyde solution was added. The reaction was carried out by heating the mixture to 94 °C once more, holding it for 25 min, and then rapidly lowering the temperature to 60 °C, to produce the PL−PF or BO−PF resins. The modified resins were then tested for pH, viscosity, solid content, FTIR, and TGA. Results revealed that the substitution of 5% PL into PF resins is enough to improve its physical properties. The PL−PF resin production process was also deemed environmentally beneficial, as it met 7 of the 8 Green Chemistry Principle evaluation criteria.